Tantangan Perlindungan Hukum terhadap Whistleblower, Saksi, dan Korban dalam Perkara Korupsi Berdasarkan Undang-Undang Nomor 13 Tahun 2014 - Tammar, La Ode Suparno; Asma, Wa Ode; Nur, Fuad (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2026)
Legal protection for whistleblowers is a crucial component in combating corruption in Indonesia. This study aims to assess the effectiveness of legal protection for whistleblowers under Article 10 of Law Number 31 of 2014 on Witness and Victim Protection, focusing on its practical implementation. Employing a normative legal research method with statutory and conceptual approaches, this study analyzes primary and secondary legal sources through prescriptive analysis. The findings reveal that, despite the existence of a legal framework granting immunity and postponement of legal proceedings for whistleblowers acting in good faith, practical implementation remains weak due to regulatory disharmony, inadequate institutional coordination, and limited capacity of the Witness and Victim Protection Agency (LPSK). These weaknesses leave many whistleblowers vulnerable to intimidation, criminalization, and social pressures. The study recommends comprehensive regulatory reform, the establishment of specific legislation, and the strengthening of institutional capacity and legal culture to ensure effective legal protection and increased public participation in anti-corruption efforts.